Program Edukasi Cyber Crime: (Pencegahan & Penanggulangan Teknik Phishing pada Kalangan Siswa/i SMP YPK Syaloom) - Melda Agnes Manuhutu; Febriani Febriani; Febi Febi; Rian Rian; Malvino Malvino; Faril Faril; Herman Herman; I Dewa Ayu Nyoman Utari Sastrani; Lulu Jola Uktolseja (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
The rapid development of information technology has increased the risk of cybercrime, particularly phishing, which poses a serious threat to adolescents who actively use digital platforms. Students of SMP YPK Syaloom were identified as a vulnerable group due to limited knowledge and awareness regarding digital security practices. This community service activity aimed to improve students’ understanding of cybercrime, with a specific focus on phishing prevention, identification, and mitigation strategies. The program was conducted through four stages: socialization, training, technology application, and mentoring with evaluation, involving approximately 10 seventh-grade students. The activities included interactive discussions, simulations of phishing cases, and practical exercises to recognize suspicious digital content. The results demonstrated a significant improvement in students’ digital security awareness, as most participants were able to identify phishing characteristics and explain appropriate prevention measures after the intervention. This activity contributed to strengthening students’ digital literacy and encouraged safer, more responsible, and ethical technology use in daily life.